Oxidative Stress Promotes Axonal Atrophy through Alterations in Microtubules and EB1 Function. - Shields, S.; Gregory, E.; Wilkes, O.; Gozes, I.; Sanchez-Soriano, N. (Aging and disease, 2024)
Axons are crucial for transmitting neurochemical signals. As organisms age, the ability of neurons to maintain their axons declines; hence, aged axons are more susceptible to damage or dysfunction. Understanding how aging causes axonal vulnerability is crucial for developing strategies to enhance overall resilience of neurons and prevent neuronal deterioration during aging and in age-related neurodegenerative diseases. Increasing levels of reactive oxygen species (ROS) causes oxidative stress - a hallmark of aging and age-related diseases. Despite this association, a causal relationship between oxidative stress and neuronal aging remains unclear, particularly in how subcellular physiology may be affected by ROS. By using Drosophila-derived primary neuronal cultures and a recently developed in vivo neuronal model of aging, which involves the visualisation of Drosophila medulla neurons, we investigated the interplay between oxidative stress, neuronal aging and the microtubule cytoskeleton. Our results showed that oxidative stress is a key driver of axonal and synaptic decay, as shown by an enhanced appearance of axonal swellings, microtubule alterations (in both axons and synapses) and morphological transformation of axonal terminals during aging. We demonstrated that increasing the levels of ROS sensitises microtubule plus end-binding protein 1 (EB1), leading to microtubule defects that effect neuronal integrity. Furthermore, manipulating EB1 proved to be a valuable therapeutic strategy to prevent aging hallmarks enhanced in conditions of elevated ROS. In summary, we demonstrate a mechanistic pathway linking cellular oxidative stress with changes in the microtubule cytoskeleton leading to axonal deterioration during aging and provide evidence of the therapeutic potential of enhancing microtubule plus-end physiology to improve the resilience of axons.